Chemical constituents from the seeds of Nigella glandulifera and their hypoglycemic activities. Issue 30 (5th July 2022) - Li, Qingqing; Xu, Jing; Chen, Yiyu; Xie, Wenli; Mei, Gui; Li, Xueni; Chen, Yu; Yang, Guangzhong
Abstract : The seed of Nigella glandulifera Freyn et Sint. is a traditional Uygur medicine used for the treatment of diabetes. Abstract : The seeds of Nigella glandulifera Freyn et Sint. are traditional Uygur medicine used for the treatment of diabetes. However, the active anti-diabetic constituents in the seeds of N. glandulifera remain unclear. In the present study, a new delabellane-type diterpene, 8-denicotinoylnigellamine A1 (1 ), and a new acyclic sesquiterpene, 2, 6, 10-trimethyl-6, 7, 12-trihydroxy-dodec-2-ene (3 ), together with eight known compounds including alkaloids (2 and 7 ), triterpenoid saponins (4–6 ), and phenolic compounds (8–10 ), were isolated from the seeds of N. glandulifera . Their structures were determined by extensive spectroscopic analyses and quantum chemical calculations. We evaluated the potential protective effects of the isolated compounds on an insulin resistant HepG2 (IR-HepG2) cell model. The results showed that compounds 2, 4–8, and 10 could promote the consumption of glucose in IR-HepG2 cells. Those compounds might be responsible for the anti-diabetic effects of the seeds of N. glandulifera .